2009
DOI: 10.1007/s00198-009-1070-3
|View full text |Cite
|
Sign up to set email alerts
|

BMD T-score discriminates trochanteric fractures from unfractured controls, whereas geometry discriminates cervical fracture cases from unfractured controls of similar BMD

Abstract: The study suggests that the risk of trochanteric fractures could be discriminated based on a BMD T-score <-2.5 criterion, whereas cervical fracture cases would remain under-diagnosed if solely using this criterion. Instead, geometrical risk factors are able to discriminate cervical fracture cases even among individuals with T-score >-2.5. For cervical and trochanteric fractures combined, BMD and geometric measures independently contributed to hip fracture discrimination. Our data support changing from T-score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Failure load was predicted less well in the stance configuration than in the side configuration. Our results are in agreement with those in several publications (23)(24)(25), some of which indicate a closer association of trochanteric fractures with low BMD than with cervical fractures, for which geometric parameters play a greater role. In our multivariate analyses, adding radiography variables to areal BMD in the total hip as measured with DXA increased the predictive performance from 73% to 80% in the stance configuration and from 82% to 84% in the side configuration.…”
Section: Descriptive Statistics and Analysessupporting
confidence: 93%
“…Failure load was predicted less well in the stance configuration than in the side configuration. Our results are in agreement with those in several publications (23)(24)(25), some of which indicate a closer association of trochanteric fractures with low BMD than with cervical fractures, for which geometric parameters play a greater role. In our multivariate analyses, adding radiography variables to areal BMD in the total hip as measured with DXA increased the predictive performance from 73% to 80% in the stance configuration and from 82% to 84% in the side configuration.…”
Section: Descriptive Statistics and Analysessupporting
confidence: 93%
“…This is in line with the findings in this and other studies (50)(51)(52) that patients with extracapsular fracture are generally older and have lower hip BMD than patients with intracapsular fracture, which lead to lower elastic modulus and yield stress of bone in our FE model. It has been shown that the current BMD-based clinical assessment procedure is adequate to predict extracapsular fracture, (53) but may underdiagnose intracapsular fracture, (54) because women with intracapsular fracture tend to have a much more complex risk profile such as longer FN length, wider neck-shaft angle, and narrower neck width than in the controls or patients with extracapsular fracture. (41)(42)(43)46,50,55) The estimated strength in this study is independently associated with both intracapsular and extracapsular fractures, its association is stronger than TH BMD and many HSA variables, and it predicts intracapsular and extracapsular fractures significantly better than TH BMD.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in FN BMD, bone strength, or LSR according to type of fracture (neck of femur or trochanteric). Some studies have suggested that trochanteric and femoral neck fractures are associated with different geometrical and density measures 37–41. Because the FE model integrates bone mass distribution and geometry information embedded in DXA scans with the loading condition known to cause hip fracture, these subtle differences are incorporated into the FE analysis model but may be canceling each other out in estimating the whole bone strength.…”
Section: Discussionmentioning
confidence: 99%